Scan time reduction for readout‐segmented EPI using simultaneous multislice acceleration: Diffusion‐weighted imaging at 3 and 7 Tesla. Issue 1 (30th July 2014) - Frost, Robert; Jezzard, Peter; Douaud, Gwenaëlle; Clare, Stuart; Porter, David A.; Miller, Karla L.
<x xml:space="preserve">Abstract</x> Purpose Readout‐segmented echo‐planar imaging (rs‐EPI) can provide high quality diffusion data because it is less prone to distortion and blurring artifacts than single‐shot echo‐planar imaging (ss‐EPI), particularly at higher resolution and higher field. Readout segmentation allows shorter echo‐spacing and echo train duration, resulting in reduced image distortion and blurring, respectively, in the phase‐encoding direction. However, these benefits come at the expense of longer scan times because the segments are acquired in multiple repetitions times (TRs). This study shortened rs‐EPI scan times by reducing the TR duration with simultaneous multislice acceleration. Methods The blipped‐CAIPI method for slice acceleration with reduced g‐factor SNR loss was incorporated into the diffusion‐weighted rs‐EPI sequence. The rs‐ and ss‐EPI sequences were compared at a range of resolutions at both 3 and 7 Tesla in terms of image fidelity and diffusion postprocessing results. Results Slice‐accelerated clinically useful trace‐weighted images and tractography results are presented. Tractography analysis showed that the reduced artifacts in rs‐EPI allowed better discrimination of tracts than ss‐EPI. Conclusion Slice acceleration reduces rs‐EPI scan times providing a practical alternative to diffusion‐weighted ss‐EPI with reduced distortion and high resolution. Magn Reson Med 74:136–149, 2015. © 2014 Wiley Periodicals, Inc.